2014
DOI: 10.2174/1871520614666140804224637
|View full text |Cite
|
Sign up to set email alerts
|

Follow the ATP: Tumor Energy Production: A Perspective

Abstract: As early as the 1920s, the eminent physician and chemist, Otto Warburg, nominated for a second Nobel Prize for his work on fermentation, observed that the core metabolic signature of cancer cells is a high glycolytic flux. Warburg averred that the prime mover of cancer is defective mitochondrial respiration, which drives a switch to an alternative energy source, aerobic glycolysis in lieu of Oxidative Phosphorylation (OXPHOS), in an attempt to maintain cellular viability and support critical macromolecular nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 96 publications
3
44
0
Order By: Relevance
“…There are four major ATP supply methods – oxidative phosphorylation, glutaminolysis, autophagy, and glycolysis. 25, 53 Combining our results shown in Figure 2c and the essential characteristics of cancer cells, we concluded that because cancer cells only maintain low levels of oxidative phosphorylation, glycolysis was blocked by the decrease in glucose, and glutaminolysis can only produce low levels of ATP, and autophagy was the likely mechanism of ATP upregulation caused by oridonin treatment. The results of autophagy-related biomarker analysis and transmission electron microscopy analysis confirmed the hypothesis (Figure 4; Supplementary Figure 3) that autophagy is induced by oridonin in p53-mutated CRC cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…There are four major ATP supply methods – oxidative phosphorylation, glutaminolysis, autophagy, and glycolysis. 25, 53 Combining our results shown in Figure 2c and the essential characteristics of cancer cells, we concluded that because cancer cells only maintain low levels of oxidative phosphorylation, glycolysis was blocked by the decrease in glucose, and glutaminolysis can only produce low levels of ATP, and autophagy was the likely mechanism of ATP upregulation caused by oridonin treatment. The results of autophagy-related biomarker analysis and transmission electron microscopy analysis confirmed the hypothesis (Figure 4; Supplementary Figure 3) that autophagy is induced by oridonin in p53-mutated CRC cells.…”
Section: Discussionsupporting
confidence: 56%
“…There are four ATP sources in normal cells, including oxidative phosphorylation, glycolysis, glutaminolysis, and autophagy. 25 The phenotype of the cancer cells indicated that oxidative phosphorylation and glutaminolysis cannot be the sources of the high intracellular ATP levels. Our finding of glucose uptake inhibition also suggested that glycolysis was not responsible for the ATP upregulation.…”
Section: Resultsmentioning
confidence: 99%
“…When the cancer cells are in a glucose-depleted condition, they maintain ATP synthesis through OXPHOS and activate the catabolic pathways, including the oxidation of fatty acids and amino acids (6,33). In addition, cancer cells are more vulnerable to ROS generally generated from mitochondria compared to normal cells (5,34).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine can be metabolized to α-KG to provide ATP through glutaminolysis [28]. Indeed, Chambers et al .…”
Section: Discussionmentioning
confidence: 99%